Roles of weapons: significance, identity and value in Anyang late Shang (c. 1200-1050 b.C.) society China - Cao, Q (2016)
Weapons of the late Shang (c.1200-1050 B.C.), characterised by their frequent discovery and various forms and materials, have often been dogmatically deciphered as either symbolic signifiers or representing military equipment. Adopting an object biographical approach, the main objective of this thesis is to employ the corpus of weapons to explore the martial facet of Shang society. Multiple strands of evidence have been compiled for the investigation: two datasets composed of over 200 complete tombs with their assemblages from the Anyang site of the late Shang, finds from non-burial contexts, the British Museum bronze weaponry collection, and contemporaneous texts. Using for the first time both statistical tools and metalwork wear analysis, this thesis challenges our understanding of the weapons of the Shang from their classification in archaeological reports to their functions and roles in society. The diverse types and materials of weapons and their multifaceted functions also shed light on interactions between objects and human beings.